Current state of heart failure treatment: are mesenchymal stem cells and their exosomes a future therapy? - Chen, Chengqian; Zhong, Wentao; Zheng, Hao; Zhao, Wei; Wang, Yushi; Shen, Botao (Frontiers in Cardiovascular Medicine, 2025)
Heart failure (HF) represents the terminal stage of cardiovascular disease and remains a leading cause of mortality. Epidemiological studies indicate a high prevalence and mortality rate of HF globally. Current treatment options primarily include pharmacological and non-pharmacological approaches. With the development of mesenchymal stem cell (MSC) transplantation technology, increasing research has shown that stem cell therapy and exosomes derived from these cells hold promise for repairing damaged myocardium and improving cardiac function, becoming a hot topic in clinical treatment for HF. However, this approach also presents certain limitations. This review summarizes the mechanisms of HF, current treatment strategies, and the latest progress in the application of MSCs and their exosomes in HF therapy.